Intercontinental hotels group -valuation in uncertain times - Melim, Maria Luísa Ornelas (2022)
This report contains a valuation completed of InterContinental Hotels Group PLC, one of the largest hospitality companies worldwide. During this Work Project, it was forecasted IHG’s future performance, its recovery and expansion following the COVID-19 pandemic and the impact of the current global economic uncertainty. To that end, analyses were conducted on macroeconomic, industry, and company-specific factors. Additionally, sensitivity analyses and relative valuation were conducted to strength the result of the DCF method. A target share price was estimated, which leads us to recommend investors to sell their positions on InterContinental Hotels Group.